2013
DOI: 10.1002/qre.1496
|View full text |Cite
|
Sign up to set email alerts
|

A t‐chart for Monitoring Multi‐variety and Small Batch Production Run

Abstract: Statistical process control is an important tool to monitor and control a process. It is used to ensure that the manufacturing process operates in the in-control state. Multi-variety and small batch production runs are common in manufacturing environments like flexible manufacturing systems and Just-in-Time systems, which are characterized by a wide variety of mixed products with small volume for each kind of production. It is difficult to apply traditional control charts efficiently and effectively in such en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…However, many modern manufacturing systems do not satisfy these assumptions [4] due to the low-volume of parts produced and/or to a high variety of mixed products. Short-run processes imply the high frequency of process setups [5].…”
Section: Spc For Short Production Runs -Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many modern manufacturing systems do not satisfy these assumptions [4] due to the low-volume of parts produced and/or to a high variety of mixed products. Short-run processes imply the high frequency of process setups [5].…”
Section: Spc For Short Production Runs -Literature Reviewmentioning
confidence: 99%
“…However, t-charts assume that at the beginning of a production run, the in-control mean is perfectly set up on the process target, or that the initial setup error, shifting the mean away from the target, is known a priori [31]. Gu et al [4] showed how t-charts can be successfully implemented in a multi-variety production run. Calzada and Scariano [32] introduced synthetic versions of the X-bar and EWMA t-charts to improve their statistical properties.…”
Section: Spc For Short Production Runs -Literature Reviewmentioning
confidence: 99%
“…According to Gu et al (2013), this method is not appropriate, since the successive state of the manufacturing process cannot be reflected and out-of-control situations may not be observed.…”
Section: Introductionmentioning
confidence: 97%
“…The warm-up is not considered in this approach as well as common variability that could be estimated through the entire series (Gu, Jia, You, & Zhang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…And the efficiency and quality of NC programming directly determine NC machining efficiency. How to improve the efficiency of NC programming is a problem in multi-varieties and smallbatch production mode [1][2][3].…”
Section: Introductionmentioning
confidence: 99%